White mulberry (Morus alba L.) fruit-associated bacterial and fungal microbiota - Juliana Lukša; Elena Servienė (Journal of Environmental Engineering and Landscape Management, 2020)
Morus alba L. has been worldwide cultivated and commercially exploited plant with profound potential in environmental management, food and medicinal industries. Plant-associated microbial communities are playing an essential role in sustainable plant development. In the present study, the bacterial and fungal microorganism populations distributed on the white mulberry fruits harvested in the Czech Republic for the first time were characterized by metagenomics approach. A total of 62 bacterial and 37 fungal families were identified on white mulberry. Bacterial population was represented by the genera Tatumella, Leuconostoc, Frateuria and Pseudomonas, while fungal microorganisms – by Hanseniaspora, Cryptococcus, Cladosporium and Phoma. Both potentially beneficial, inducing resistance in the hosting plant, and pathogenic, responsible for disease development, microorganisms were detected. The information on the prevalence of bacterial and fungal microorganisms on the carposphere of M. alba is highly relevant for the development of strategies for environment-friendly plant cultivation, disease management and prevention.